Binary and Ternary Colloidal Cu‐Sn‐Te Nanocrystals for Thermoelectric Thin Films. Issue 11 (24th February 2021) - Yin, Deqiang; Dun, Chaochao; Zhang, Huisheng; Fu, Zheng; Gao, Xiang; Wang, Xianliang; Singh, David J.; Carroll, David L.; Liu, Yang; Swihart, Mark T.
Abstract: Recent advances in copper chalcogenide‐based nanocrystals (NCs), copper sulfide, and copper selenide derived nanostructures, have drawn considerable attention. However, reports of crystal phase and shape engineering of binary or ternary copper telluride NCs remain rare. Here, a colloidal hot‐injection approach for producing binary copper/tin telluride, and ternary copper tin telluride NCs with controllable compositions, crystal structures, and morphologies is reported. The crystal phase and growth behavior of these tellurides are systematically studied from both experimental and theoretical perspectives. The morphology of Cu1.29 Te NCs is modified from 1D nanorods with different aspect ratios to 2D nanosheets and 3D nanocubes, by controlling the preferential growth of specific crystalline facets. A controllable phase transition from Cu1.29 Te to Cu1.43 Te NCs is also demonstrated. The latter can be further converted into Cu2 SnTe3 and SnTe through Sn incorporation. Temperature dependent thermoelectric properties of metal (Cu and Sn) telluride nanostructure thin films are also studied, including Cu1.29 Te, Cu1.43 Te, Cu2 SnTe3, and SnTe. Cu2 SnTe3 is a low carrier density semimetal with compensating electron and hole Fermi surface pockets. The engineering of crystal phase and morphology control of colloidal copper tin telluride NCs opens a path to explore and design new classes of copper telluride‐based nanomaterials for thermoelectrics and other applications. Abstract : The crystal phase and growth behavior of copper‐tin‐telluride nanocrystals are systematically studied from both experimental and theoretical perspectives, producing Cu1.29 Te, Cu1.43 Te, Cu2 SnTe3, and SnTe with various morphologies. Cu2 SnTe3 shows an outstanding electrical conductivity of 2.5 × 10 5 S m −1 at 50 K, with a stable Seebeck coefficient over a wide temperature range.